Employing Picture Word Inductive Model to Improve Undergraduate Students Writing Ability in Online Learning - Lailiy Kurnia Ilahi; Johannes Ananto Prayogo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
This research is intended to improve undergraduate students’ ability in writing descriptive paragraphs by employing the picture word inductive model (PWIM) in online learning. This study involved the 29 students of Intensive Course Writing program of Universitas Negeri Malang 2021 cohort. This Classroom Action Research was conducted in one cycle which consisted of five meetings. In collecting the data, the researcher employed four instruments namely the writing test, scoring rubrics, classroom observation checklist, and field notes which had been previously validated. The finding of this research indicated that the employment of could improve students’ writing ability in descriptive paragraphs since it has successfully fulfilled the criteria of success which is 80% of the students got or achieved the passing grade, 75. Therefore, for the teachers who experiences similar issues, the implementation of this strategy can be taken into consideration as one of the alternative ways to improve students’ writing in online learning. For further research in the same realm, it is suggested to employ the result of the research of this study as one of the valid references in conducting the research.